BENTUK DAN SIFAT PENGABDIAN MASYARAKAT YANG DITERAPKAN OLEH PERGURUAN TINGGI - Herlina Emilia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The drama of community service by universities is often connoted as an activity of providing free assistance and services to community groups who are weak, economically incapable, and are in a state of backwardness. Such connotations are the result of an error in interpreting the term